PROPERTIES OF THE k-TH UPPER ORDER STATISTICS PROCESS THROUGH AN EXAMPLE - Gacovska-Barandovska, Aneta (Matematichki Bilten, 2019)
The author has previously considered the asymptotic behavior of upper order statistics with central rank of a sample with deterministic size and of randomly indexed upper order statistics. In this paper, by using regular norming time-space changes, a theoretical example has been constructed in order to illustrate some of the obtained properties of the \(k\)-th upper order statistics process.